Analysis of a plastic injection process by fluid-structural interaction and state change - Páramo, Jorge Jurado; Reveles Arredondo, Juan Francisco; Mora, Héctor Plascencia; Gómez, Eduardo Aguilera (Acta Universitaria, 2019)
This paper proposes a methodology to simulate the injection molding process. The methodology enables a fluid-structural interaction (FSI) analysis for the mold and phase change for the injected part. The simulation was conducted in ANSYS Workbench® 14.5. Simulation for injection stage was conducted in the modules CFX® and Fluent® to carry out a comparison. The resulting pressure and temperature were exported to the Mechanical® module for a thermo-structural analysis of the mold and a phase change for the part. The proposed methodology was validated experimentally, resulting in an error of 2% for injection pressure with experimental results and 6% for the part surface temperature. The proposed methodology can assist in calculating important parameters such as pressure and temperature for injection. Results from structural analysis include stresses and strains in the mold as well as necessary closing force; these results are expected to lead to improved molds design.